Analisis Semiotika Pesan Dakwah dalam Film Horor “Hidayah” - Riska Sari; Andi Adhe Surya Haruna; Andi Dwi Maisarah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
The aim of this research is to enhance spiritual awareness, strengthen faith, and encourage people to behave positively. In the horror film "Hidayah," using Roland Barthes' semiotic approach, this research employs a qualitative descriptive method. The horror film "Hidayah" tells the story of Bahri, a young cleric, who tries to bury his past while working in the city. However, after returning to Mekarwangi village, where he was raised, he experiences supernatural events. According to the results of this research, the film "Hidayah" contains messages of Sharia, morality, and faith as part of its religious teachings.